Utilization of copper sulphide nanoparticles for the development of cashew tree gum/ chitin biopolymer blend nanocomposites. (March 2023) - Ramesan, MT; Subburaj, M; Mathew, G; Bahuleyan, BK
This work focused on the preparation of biopolymer blend nanocomposites from chitin (CT) and cashew tree gum (CTG) with different contents of copper sulphide nanoparticles (CuS) by solution casting method. The formation of nanocomposites have been characterized by FT infrared (FTIR), UV spectroscopy, X-ray diffraction (XRD), scanning electron microscope (SEM), high-resolution transmission electron microscope (HRTEM), thermogravimetry (TGA), differential scanning calorimetry (DSC) and impedance analysis. The characteristic absorption of nanoparticles in the FTIR spectra and shift in UV spectra of blend composites revealed the strong interaction between CuS nanoparticles and the polar segments of CT/CTG blend. With the increase in dosage of nanoparticles, a decrease in amorphous domains has been noted in the XRD scans. The uniform distribution of nanoparticles in CT/CTG network has been confirmed by the SEM analysis. HRTEM of the blend composites reveals the formation of hemispherical nanoparticles with a diameter of 15–30 nm. The glass transition temperature of blend composites increased with the addition of nano-CuS in the polymer matrix. Compared to the pure CT/CTG blend, the prepared nanocomposite showed higher thermal stability. Mechanical properties such as tensile strength and hardness of the blend nanocomposites were greatly enhanced by the reinforcement of CuS into the CT/CTG matrix. The AC conductivity and dielectric properties of the nanocomposites increased with the concentration of fillers and the magnitude of these properties was higher than the pure polymer blend.